The National United States Center Data Repository: Core essential interprofessional practice & education data enabling triple aim analytics. Issue 6 (3rd November 2015) - Pechacek, Judith; Shanedling, Janet; Lutfiyya, May Nawal; Brandt, Barbara F.; Cerra, Frank B.; Delaney, Connie White
Abstract: Understanding the impact that interprofessional education and collaborative practice (IPECP) might have on triple aim patient outcomes is of high interest to health care providers, educators, administrators, and policy makers. Before the work undertaken by the National Center for Interprofessional Practice and Education at the University of Minnesota, no standard mechanism to acquire and report outcome data related to interprofessional education and collaborative practice and its effect on triple aim outcomes existed. This article describes the development and adoption of the National Center Data Repository (NCDR) designed to capture data related to IPECP processes and outcomes to support analyses of the relationship of IPECP on the Triple Aim. The data collection methods, web-based survey design and implementation process are discussed. The implications of this informatics work to the field of IPECP and health care quality and safety include creating standardized capacity to describe interprofessional practice and measure outcomes connecting interprofessional education and collaborative practice to the triple aim within and across sites/settings, leveraging an accessible data collection process using user friendly web-based survey design to support large data scholarship and instrument testing, and establishing standardized data elements and variables that can potentially lead to enhancements to national/international information system and academic accreditation standards to further team-based, interprofessional, collaborative research in the field.